Gender roles and leadership styles: an empirical evaluation of senior executive teams of public universities in Gauteng Province, South Africa - Alahdal, Kamal (My University, 2018)
The objective of this dissertation was to investigate the influence of gender roles on leadership styles, with regards to senior management staff at universities in Gauteng province. Women represent 51.1% of the South African population (Statistics South Africa, 2015), but their position in the workplace is still marginalised. Representation of women in senior management positions in South African universities are relatively low. Women are still marginalised in terms of progression to senior management positions, due to a number of factors including glass ceiling, and the leadership style adopted (Kayi, 2013). The Council of Higher Education (2013) reports that a total of 2664 senior management staff were employed across 23 public universities in South Africa, of which 1510 (56%) were men and 1154 (44%) were women. The study investigated the barriers that inhibit the progression of women to senior management positions and how leadership styles contribute to the gender gap within senior management. Theories such as the role congruity, think manager – think male paradigm and the social role theory provide theoretical grounding for the study. With regards to the research methodology, qualitative research techniques was utilised. Fourteen participants were chosen to participate in the study. The snowball sampling technique was utilised for this study. Data was analysed using thematic analysis, which includes familiarization, developing a thematic framework, indexing and mapping and interpretation. This study is limited to senior management staff, at universities within the Gauteng province; therefore, the findings of the study may not be generalizable to other universities in South Africa. The findings demonstrate that while all the respondents identify as being transformational leaders, it is necessary to develop and understand when to enforce transformational and transactional behaviours. Therefore, the environment in which one operates in and the circumstances encountered by leader’s influences leadership behaviours. The findings illustrate that woman in senior management positions are perceived to be underrepresented but only in certain roles and positions. There is a good representation of female leaders but it is the top management positions where males still dominate. Although the female leaders have experienced some barriers in their career progression, there is a general belief that gender stereotyping is becoming less of an issue. The respondents mentioned training, coaching and mentorship, workshops for men as well as monitoring legislations/equality targets as recommendations to addressing the gender imbalance within senior management teams.
A dissertation submitted to the Faculty of Commerce, Law and Management, University of the Witwatersrand, Johannesburg, in fulfilment of the requirements for award of the degree of Master of Commerce (Human Resource Management) in the School of Economic and Business Sciences, May 2018
Keywords: Educational leadership--South Africa; Leadership; Women in education